Mechanical twinning in phosphorene. (March 2018) - Sorkin, V.; Cai, Y.Q.; Srolovitz, D.J.; Zhang, Y.W.
Abstract: We investigate the deformation and failure mechanisms of phosphorene sheet and nanoribbons under uniaxial tensile strain along the zigzag direction using the density functional tight-binding method. Surprisingly, twinning occurs homogeneously across the phosphorene sheet; which significantly increases its failure strain. Vacancies within the sheet lead to the heterogeneous nucleation of twins at a lower critical strain which, subsequently, propagate across the entire sheet. Twinning always occurs heterogeneously in phosphorene nanoribbons (with or without vacancies). Propagation of the twins is interrupted by fracture which initiates along the ribbon edge. The underlying twinning mechanism is bond breaking between the atoms within phosphorene puckers and simultaneous bond formation between the atoms in neighboring puckers. This unusual deformation behavior in phosphorene may be exploited in novel nano-electronic-mechanical applications. Highlights: Twinning is a fundamental deformation mechanism in crystalline materials. In 3D nanostructures, twinning is frequently observed, but never before in 2D materials. This raises a fundamental question: is mechanical twinning possible in 2D materials? We report the first observations of twinning in phosphorene sheets and nanoribbons. We believe that our study potentially opens new areas of research and applications of 2D materials.